2016
DOI: 10.1016/j.acthis.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Lipid droplets in cultured luteal cells in non-pregnant sheep fed different planes of nutrition

Abstract: Accumulation of lipid droplets (LD) in luteal cells likely is important for energy storage and steroidogenesis in the highly metabolically active corpus luteum (CL). The objective of this study was to determine the effect of plane of nutrition on progesterone (P4) secretion, and lipid droplet number and size in cultured ovine luteal cells. Ewes were randomly assigned to one of three nutritional groups: control (C; 100% NRC requirements, n=9), overfed (O; 2×C, n=12), or underfed (U; 0.6×C, n=10). Superovulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 63 publications
4
7
0
Order By: Relevance
“…45,46 The LIPE/HSL mRNA transcripts were enriched 2-fold in small luteal cells compared to theca cell counterparts (P < .05; Figure 1A); and 2.7-fold in large luteal cells when compared to granulosa cells (P < .05; Figure 1A). In keeping with the presence of lipid droplets in luteal cells, 23 large and small luteal cells had 2.3-fold and 4-fold greater PLIN2 transcripts than granulosa and theca cells, respectively (P < .05; Figure 1A). Moreover, STAR transcripts were elevated by 1.4-fold in small luteal cells compared to theca cells (P < .05; Figure 1A); however, we observed much greater transcript expression of STAR in large luteal cells (56-fold) when compared to granulosa cells ( Figure 1A), which is in keeping with the conversion from an estrogen secreting granulosa cell to a progesterone manufacturing luteal cell.…”
Section: Expression Of Hsl Plin2 and The Key Components Of Steroisupporting
confidence: 59%
“…45,46 The LIPE/HSL mRNA transcripts were enriched 2-fold in small luteal cells compared to theca cell counterparts (P < .05; Figure 1A); and 2.7-fold in large luteal cells when compared to granulosa cells (P < .05; Figure 1A). In keeping with the presence of lipid droplets in luteal cells, 23 large and small luteal cells had 2.3-fold and 4-fold greater PLIN2 transcripts than granulosa and theca cells, respectively (P < .05; Figure 1A). Moreover, STAR transcripts were elevated by 1.4-fold in small luteal cells compared to theca cells (P < .05; Figure 1A); however, we observed much greater transcript expression of STAR in large luteal cells (56-fold) when compared to granulosa cells ( Figure 1A), which is in keeping with the conversion from an estrogen secreting granulosa cell to a progesterone manufacturing luteal cell.…”
Section: Expression Of Hsl Plin2 and The Key Components Of Steroisupporting
confidence: 59%
“…Small luteal cells have a mean LD volume 2.4 times greater than large luteal cells; whereas, large luteal cells have three times the number of LDs present in small luteal cells. This finding is in agreement with data by Khanthusaeng et al, who found that ovine large luteal cells have many smaller LDs and small luteal cells have fewer, but larger LDs (43). The difference in LD size and number in the two cell types may relate to the different functions of large and small luteal cells.…”
Section: Discussionsupporting
confidence: 93%
“…Luteal LDs are a prominent feature of bovine luteal tissue and the presence, prominence, and composition of luteal Luteal tissue of all examined species contain abundant LDs which vary in size and number throughout the normal estrous or menstrual cycle (15)(16)(17)(18)(19). The findings that neutral lipids occupy approximately 5-16% of bovine luteal tissue area is in agreement with other studies examining LD to luteal cell area or volume (27,28,43). In contrast, other tissues rarely contain the same amount of neutral lipids, except during pathological situations (8)(9)(10)(11).…”
Section: Discussionsupporting
confidence: 88%
“…Luteal tissue of all examined species contain abundant LDs, which vary in size and number throughout the normal estrous or menstrual cycle [14][15][16][17][18] . The findings that neutral lipids occupy approximately 5-16% of bovine luteal tissue area is in agreement with other studies examining LD to luteal cell area or volume 26,27,33 . In contrast, other tissues rarely contain the same extant of neutral lipids, except during pathological situations [8][9][10][11] .…”
Section: Composition Of Isolated Luteal Ldssupporting
confidence: 92%